Prevalence of appropriate feeding practices and nutritional status among infant and young children aged 0–23 Months attending public hospitals in Harar town, eastern Ethiopia, 2024: An institutional-based cross-sectional study - Samuel Demissie Darcho; Feyisa Shasho Bayisa; Teshome Demis Nimani (Clinical Epidemiology and Global Health)
Introduction: Appropriate feeding is a set of recommendations to achieve optimal infant and young child feeding practices for 0-23-month-old children. Inappropriate infant and young child feeding (IYCF) practices are the leading cause of malnutrition in children. This study aimed to assess the prevalence of appropriate feeding practices and nutritional status among infants and young children aged 0–23 months attending public hospitals in Harar town, eastern Ethiopia. Methods: An institutional-based cross-sectional study was conducted among 216 mothers of children aged 0–23 months from July 1 to 30, 2024. A simple random sampling technique was used to select the respondents. Data was collected using a structured interviewer-administered questionnaire. Results: In this study, the overall prevalence of appropriate infant and young child feeding (IYCF) practice was 83.8 % (95 % CI: 78.7, 88.9). The study results also showed that the prevalence of severe undernutrition, stunting, wasting, and severe acute malnutrition was 14.4 % (95 % CI: 9.7, 19.4), 20.4 % (95 % CI: 15.3, 25.9), 13.9 % (95 % CI:10.2,19.0), and 13.9 % (95 % CI:2.3, 7.9), respectively. Conclusion: In the current study, the majority of the young and infant children aged 0–23 months had appropriate feeding practice and good nutritional status. It is recommended that early assessment of the nutritional status of infants and children, and all the necessary interventions, such as health education on breastfeeding, complementary feeding, and meal preparation, should be given to mothers.